2009
DOI: 10.1162/ling.2009.40.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Equal Treatment for All Antecedents: How Children Succeed with Principle B

Abstract: Children have repeatedly been found to exhibit Principle B violations, with some reports that these violations occur only with nonquantified antecedents. This quantificational asymmetry (QA) in the delay of Principle B effect (DPBE) has been taken as support for a theory that restricts the scope of binding theory to bound variable anaphora (Reinhart 1983). However, the QA has been challenged, on the basis of discrepant findings and methodological concerns (Elbourne 2005). Here, we resolve the status of the QA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
92
2
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 33 publications
(47 reference statements)
6
92
2
8
Order By: Relevance
“…found that children do not perform better with quantifier binding (Conroy et al, 2009;Matthews et al, 2009). This casts serious doubt on the theoretical distinction between variable binding and coreference in pronoun interpretation.…”
Section: Asymmetries As a Results Of Lack Of Pragmatic Knowledgementioning
confidence: 98%
See 2 more Smart Citations
“…found that children do not perform better with quantifier binding (Conroy et al, 2009;Matthews et al, 2009). This casts serious doubt on the theoretical distinction between variable binding and coreference in pronoun interpretation.…”
Section: Asymmetries As a Results Of Lack Of Pragmatic Knowledgementioning
confidence: 98%
“…Several studies (e.g., Bloom et al, 1994;Conroy et al, 2009) have adopted this line of argumentation to dismiss the comprehension results in favor of the production results. These studies conclude that children do possess the relevant knowledge of grammar, even though they make errors in comprehension experiments.…”
Section: Asymmetries As An Experimental Artifactmentioning
confidence: 99%
See 1 more Smart Citation
“…As established in a variety of comprehension studies (e.g., Wexler & Chien 1985), children typically interpret reflexive pronouns correctly more than 95% of the time from a very early age (as young as age 3). In contrast, performance on plain pronouns during the same period is usually significantly lower, hovering between 50% and 85%, depending on how carefully the supporting contexts are constructed (Conroy et al 2008). Moreover, typical errors involve interpreting the pronoun in patterns such as Donald Duck washed him as coreferential with the subject-i.e., as if it were a reflexive pronoun.…”
Section: The Problem Of Language Acquisitionmentioning
confidence: 99%
“…This literature is characterized by numerous methodological issues (see extensive discussions in Conroy, Takahasi, Lidz, & Phillips, 2009;Elbourne, 2005;Grimshaw & Rosen, 1990). In truth-value judgment tasks, the experimenter acts out a scene, a puppet or the experimenter makes a statement, and the child judges the statement as true or false in relation to the acted out scene.…”
mentioning
confidence: 99%